Corporate Governance exercised through the delicate balance between Shareholder’s rights and Board roles in Europe - Ngcetane-Vika, Thelela (My University, 2023)
Corporate governance is fundamental to well-run organisations. Accordingly, it is associated with the positive performance of corporations and international best practices. It is the blueprint that helps shareholders scope their activities and engagement within a company, including the role and structures of the Board of Directors (BoD). It is against this backdrop that the BoD is the nexus between executive leadership and corporate governance, a hallmark of an effective functioning corporation and the affirming of an integrative approach. Thus, good corporate governance is arguably an important tool in curbing corporate malfeasance and limiting scandals in corporations. Conversely, poor corporate governance is observed when there are lapses in this relationship between shareholder‘s rights and board roles. Invariably, this leads to corporate lapses and scandals. Europe has made strides in corporate governance, through its developing legislative framework. Pursuantly, corporate governance theories exercised in Europe posit ownership and management as key variables to achieving well-run organizations. Thus, central to corporate governance is the principle of separation of ownership and management. In tandem with this view, good corporate governance is achieved through the delicate balance of the rights of shareholders as owners of the company and the roles of directors who have the duty to run the affairs of the company, as enshrined in the Statute governing Company law. The empirical basis for this paper has included collecting data mostly from primary and secondary sources, including literature review on books, articles, caselaws and relevant Statutes. The paper contributes to theory, practice, and policy formulation but specifically, to the importance of shareholders’ rights and board roles in corporate governance in Europe. Similarly, policymakers could find these insights useful to inform evidence-based practices and policymaking
Keywords: Board roles; Corporate Governance; Separation of Ownership and Control; Shareholder’s rights